PETROLOGY AND GEOCHEMISTRY OF ROCKS FROM THE BASEMENT OF THE PECHENGA PALEORIFT - Vetrin V.R.; Turkina O.M.; Ludden J. (My University, 2002)
The basement of the Early Proterozoic Pechenga paleorift was penetrated by the Kola Superdeep Borehole over a depth interval of 6842-12,261 m. The principal types of basement rocks are gneisses of trondhjemite-tonalite composition in association with amphibolites, gneisses containing aluminous minerals, and banded iron formation (BIF). It was demonstrated that the paleorift basement and rock associations exposed at the surface in the northwestern part of the Kola-Norwegian block are of similar age, composition of their protoliths, and correspond to the main types of sedimentary-volcanic and plutonic rocks of the Archean granite-greenstone terrane, which was broken up into separate segments in the Early Proterozoic. Rocks of the Pechenga Archean basement were affected by Proterozoic magmatism and metasomatism related to the rift development. The most intense Proterozoic processes in the Pechenga basement and its nearest surroundings were intrusion of numerous mafic-ultramafic bodies, retrograde metamorphism to the medium-low-temperature amphibolite and epidote amphibolite facies, synmetamorphic migmatization, and emplacement of postkinematic granite dikes. Most Proterozoic processes were determined to have been related to mantle sources. The overall amounts of Proterozoic material introduced into the Archean rocks penetrated by the lowermost part of the borehole plus the remobilized Archean crustal material were estimated at 30% ( 12-15% amphibolites, ~3% granite veins, and ~15% migmatized rocks).
Keywords: PETROLOGY AND GEOCHEMISTRY OF ROCKS; PECHENGA PALEORIFT; KOLA SUPERDEEP BOREHOLE; Proterozoic; Archean; Precambrian::Proterozoic; Precambrian::Archean; Докембрий::Архей; Докембрий::Протерозой